2015
DOI: 10.3389/fimmu.2015.00501
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of APC Function and Anti-Tumor Immunity by Anti-Cancer Drugs

Abstract: Professional antigen-presenting cells (APCs), such as dendritic cells (DCs), are central to the initiation and regulation of anti-cancer immunity. However, in the immunosuppressive environment within a tumor APCs may antagonize anti-tumor immunity by inducing regulatory T cells (Tregs) or anergy of effector T cells due to lack of efficient costimulation. Hence, in an optimal setting, anti-cancer drugs have the power to reduce tumor size and thereby may induce the release of tumor antigens and, at the same time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 88 publications
2
27
0
Order By: Relevance
“…It has recently been shown that certain cytotoxic agents can mediate an immunogenic tumor cell death [44,45]. In addition, certain immunostimulatory agents (e.g., antibody-cytokine fusion proteins, immunological check-point inhibitors) may potently synergize with some cytotoxic agents [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that certain cytotoxic agents can mediate an immunogenic tumor cell death [44,45]. In addition, certain immunostimulatory agents (e.g., antibody-cytokine fusion proteins, immunological check-point inhibitors) may potently synergize with some cytotoxic agents [46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Not only do such ADCs induce immunogenic cell death, but the ADC-mediated tumor accumulation of a potent microtubule agent appears to activate intra-tumor dendritic cells, inducing uptake of antigens and the migration of antigen-loaded dendritic cells to lymph nodes where they can trigger activation of T-cells which may be directed towards tumor-associated antigens [92–95]. Pre-clinically, MĂŒller et al have demonstrated that T-DM1 renders HER2-positive breast cancer highly susceptible to checkpoint blockade [94].…”
Section: The Place Of Adcs In the Treatment Of Solid Tumorsmentioning
confidence: 99%
“…ICD results in the release of tumor antigens and “danger signals,” also known as damage-associated molecular patterns (DAMPS), such as calreticulin, ATP, type I IFN, and non-histone chromatin-binding protein high-mobility group box 1 (HMGB1) (30, 31). Binding to their receptors (CD91, the purinergic receptors P2RX7 and P2RY2, IFNAR, and the toll-like receptor TLR4, respectively) on DCs, results in their activation, enhanced antigen presentation, upregulation of co-stimulatory receptors, and induction of adaptive immune responses (32), whereas cell death that is “immunologically silent” induces tolerance.…”
Section: Combinations With Stimulation Of Antigen Release and Danger mentioning
confidence: 99%